EVOLUTION OF BELTS FROM BRONZE AGE TO MODERN FASHION STATEMENTS - Rajeswari, Allu Poshitha; Greeshma, S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Across history, belts have evolved from their practical beginnings to become potent emblems of prestige, style, and cultural expression. Belts have come a long way from their utilitarian origins as instruments for carrying weapons in the Stone Age to their current position as opulent fashion accessories. The historical development of belts is examined in this essay, along with their functions in prehistoric times, the Middle Ages, the Renaissance, and the Modern Era. It explores the social significance of belts, how their form and function have evolved, and how they have continued to impact fashion trends. The study also addresses future directions and present trends in belt design, including technical advancements, cultural influences, and sustainability initiatives. By use of a historical context and current development analysis, this paper delves into the history of belts and its future trends and advancements.